Учет неопределенности информации при составлении планов ликвидации аварий угольных шахт - Кокоулин, И.Е. (Геотехническая механика, 2009)
Визначено, що існуючі методи складання оперативної частини ПЛА орієнтовані на аналітичний підхід до вироблення мір по ліквідації аварій, ускладнені неможливістю, на етапі використання „великих” ЕОМ, організації діалогу „користувач - ЕОМ”, і тому необхідно розробити додаткові методи врахування невизначеності інформації під час розробки ПЛА та спрощення критеріїв вибору аварійного вентиляційного режиму з урахуванням підвищення можливостей його оптимізації на сучасних ПЕОМ. Зроблено висновки щодо можливості та оцінки хиб методів iмiтацiйного моделювання аварійної ситуації (екзогенної пожежі) з метою вироблення мір по складанню та викристанню ПЛА. Marked, that existing method of working jun of operation part of PLA oriented to the analitical method of approach to the elaboration of measures for liquidation of accidents, which complimated of impossibility, at the stage of use of “large” ECM, organization of dialogue “technologist-ECM”, and that’s why is need to device a complementary methods of calculation indefinity of information in the time of wjrking out of PLA and simplification criterions alternative of repair ventilation regime with the calculation of possibilities of it’s optimization on the contemporary personal ECM. Drawed a cconclusions about possibility and estimation mistakes of methods of imitated modelling of repair situation (exogen fire) with the purpose elaboration of measures for the working out and
use of PLA.